UNIQUE MEMOIRS OF UKRAINE'S POST OFFICE - Орехова, Светлана (SWorldJournal, 2020)
The article is devoted to unique monuments in the history of postal services in Ukraine. The conditions of creation of the Mariupol Zemsky Post and the Bakhmut district of Katerynoslav Province at the end of XIX - beginning of XX centuries are analyzed.